Preference of Social Media Usage in Teenagers Religion - Retpitasari, Ellyda; Oktavia, Nila Audini (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This study discusses the use of social media in teenagers. Teenagers are a period of searching for identity and God's presence is a major issue in teenagers. Teenager’s life trying to meet the needs of religious information possessed from outside through social media. Religious information on social media affects teenager religiosity which is reflected in religious maturity and religious commitment. Research on social media, religious maturity and religiosity commitment used a comparative quantitative approach with descriptive-analytical methods. The subjects were 40 students in a private high school in Sidoarjo. The results showed that social media use is related to religion maturity and teenager religious commitment. Social media are often used as religious references by teenagers include, WhatsApp, Instagram, and Facebook. Variation in social media using among teenagers has affected variation teenagers on the level of religious maturity and religiosity commitment. Such as condition correspondents with the theory of uses and gratification which makes users an active agent in establishing social media use as a reference. Increasingly, the difference in the level of religious maturity and religiosity commitment is contingent on hope and satisfaction of any use in assessing the social media account referenced to Da’wa.